Role of centchroman versus danazol in treatment of benign breast disorders - Khoja, Hanuman Ram; Barala, Bodu Ram; Sharma, Saurabh; Om, Prabha; Saini, Devendra (International Surgery Journal, 2021)
Background: The breast is a dynamic structure that undergoes cyclical changes throughout the menstrual cycle. Any aberration from normal physiological changes in breast produces different problem in breast. Many drugs are used for treatment for these disorders like Danazol, Bromocriptine, Tamoxifen and LH-RH analogue but still no consensus for any drug is present. Methods: The aim of our study was to analyze the effectiveness of drug Centchroman and its comparison with Danazol in treatment of benign breast disorders in respect to symptoms relief, decrease in nodularity and lump size, recurrence, cost and side effects of drug. This prospective study was conducted on 250 patients of benign breast disorders attending surgical OPD between May 2018 to September 2019 in SMS medical college and Hospital, Jaipur. Results: Tolerance and improvements in symptoms in centchroman group was more than danazol (100% vs 92.8%) with less recurrence in former group. While side effects varied between the two groups with menstrual irregularities more common in centchroman group. Conclusions: The study shows that centchroman is safe, more effective and less expensive to Danazol for the treatment of benign breast disorders in long term.